PEMBUATAN GAME SHOOT ‘EM UP “STOP THE ALIENS” DENGAN FITUR ACCELEROMETER MENGGUNAKAN UNITY BERBASIS ANDROID - Victor Christian Tania; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
In this game players act as an airplane which shoots and avoids aliens. This game is developed for Android based smartphones. This game was made using the Unity game engine with C# as the programming language. This game is endless with difficulty increasing as time goes by. The goal is to get the highest score. The player has to tilt the smartphone to control the character. Testing is done by the blackbox method, alpha testing, and beta testing. The test results show that "Stop The Aliens" is a game that is not too hard and fun with interesting controls.